Implementasi Penerimaan Peserta Didik Sekolah Khusus Olahragawan SMP/SMA Negeri Ragunan Jakarta - Salamah, Siti Afiyatus; Anjaryani, Siwi (Universitas Indraprasta PGRI Jakarta, 2024)
The enrollment of new students (PPDB) at SMP/SMA Negeri Ragunan Jakarta for the 2023/2024 academic year is conducted in May-August 2023. This PPDB process differs from regular schools because this school is specialized for athletes. This study aims to explain the implementation of PPDB at SMP/SMA Negeri Ragunan Jakarta, using a descriptive qualitative research method. The results of this study indicate that the process and procedures for implementing PPDB at SMP/SMA Ragunan are already good in adhering to the specified PPDB standards. This article is expected to provide feedbacks to relevant parties to conduct an evaluation of the PPDB implementation to make it even better than before and to increase awareness among external communities regarding the PPDB process at SMP/SMA Negeri Ragunan Jakarta.